Big Data Management Optimization for Managerial Decision Making and Business Strategy - Ali, Rizwan; Darmawan, Didit (Journal of Social Science Studies, 2023)
The application of data analytics and big data in managerial decision-making and business strategy has become a critical element that determines an organization's success in the digital age. Big data allows companies to glean deeper insights into their customers, market trends, as well as operations, which ultimately helps in formulating more evidence-based decisions. A major challenge that organizations face is how to effectively manage and integrate this big data. Data quality, limited analytics skills and adequate technology infrastructure are obstacles that need to be overcome for companies to optimally utilize the potential of big data. It is important for companies to invest in human resource skills development and improve technology infrastructure. Companies must create a culture that supports data-driven decision-making throughout the organization. Thus, management of big data can create a sustainable competitive advantage, help companies formulate more accurate strategies, and improve the overall customer experience.